2008
DOI: 10.1080/17457300802423224
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of intimate partner violence against women and HIV/AIDS: a review

Abstract: The objective of this study was to review original research on the intersection of violence against women by intimate partners and risk for HIV infection and highlight opportunities for new research and programme development. Seventy-one articles presenting original, peer-reviewed research conducted with females aged 12 years and older in heterosexual relationships during the past decade (1998–2007) were reviewed. Studies were eligible for inclusion if they addressed intimate partner violence (IPV) against wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
328
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(353 citation statements)
references
References 84 publications
11
328
2
6
Order By: Relevance
“…Experiencing domestic violence has been found to be an important trauma type associated with PTSD and CMDs (Kaminer, Grimsrud, Myer, Stein, & Williams, 2008; Schumm, Briggs-Phillips, & Hobfoll, 2006). There is evidence showing high rates of PTSD among victims of domestic violence (Campbell et al, 2008; Dutton et al, 2006; Machtinger, Wilson, Haberer, & Weiss, 2012). Our results support findings that physical assault and interpersonal violence are common in a population with a high HIV prevalence (Davis, 2012; Kouyoumdjian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Experiencing domestic violence has been found to be an important trauma type associated with PTSD and CMDs (Kaminer, Grimsrud, Myer, Stein, & Williams, 2008; Schumm, Briggs-Phillips, & Hobfoll, 2006). There is evidence showing high rates of PTSD among victims of domestic violence (Campbell et al, 2008; Dutton et al, 2006; Machtinger, Wilson, Haberer, & Weiss, 2012). Our results support findings that physical assault and interpersonal violence are common in a population with a high HIV prevalence (Davis, 2012; Kouyoumdjian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of the literature revealed several mechanisms that link these women's health problems and empirical data have supported these associations. [5][6][7][8] Women who are forced to have sex with an HIV-positive partner could be exposed to infection, and living with violence or the fear of abuse by an intimate partner can limit women's ability to negotiate safe sex behaviors. [9][10][11][12][13][14][15][16] Conversely, women who are HIV-positive might experience abuse upon disclosure of their HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…Outro aspecto a ser considerado é que quando a mulher solicita um exame de HIV, compartilha seu status sorológico com o parceiro, solicita o uso do preservativo na relação sexual com o parceiro fixo para prevenir doenças, ou quando precisa tomar decisões sobre uma gravidez até o momento em que busca tratamento para si ou para o parceiro ou para a prevenir a transmissão vertical do HIV para seu bebê, ela também pode ser alvo de violência por sua condição sorológica (Campbell et al, 2008). Santos et al (2009) verificaram que, embora apenas 2% das mulheres vivendo com HIV tenham relatado a violência sexual como categoria de exposição ao vírus, 22,1% dessas mulheres apresentam histórico de violência sexual alguma vez na vida, enquanto em mulheres soronegativas esse índice cai para 13,2%.…”
Section: Introductionunclassified